Pengaruh Problem Based Learning (PBL) Dalam Meningkatkan Kompetensi Mahasiswa Program Studi Pendidikan Kimia FKIP UPR Sebagai Calon Guru - Suandi Sidauruk (Jurnal Ilmiah Kanderang Tingang, 2019)
The implementation of PBL will help students develop the habits of thinking, attitude and behavior needed as professional educators who are competent, serving, and ethical. If done correctly, PBL can make an important contribution to improving teacher character. The purpose of this study is to develop PBL scenarios and determine the effect of PBL learning on increasing student competency as teacher candidates. PBL scenario development is done through logical review. Logical review aims to determine the validity of the case and steps to solve the case using the seven jump method. The results of this study are PBL scenarios for chemistry education research methods courses. The main obstacle in implementing PBL learning is that students' knowledge related to the concept of chemistry is very low, so students have difficulty identifying the problems raised in the case. Overall, students are able to formulate problems and research titles correctly even though the chemical substance under study is not yet understood. PBL learning is appropriate for subjects whose standard competencies demand student competencies in producing something.